Approximate Asymptotic Distribution Functions for Unit Roots and Cointegration Tests - James G. MacKinnon (Queen's University, Department of Economics, 1992)
This paper uses Monte Carlo experiments and regression methods to calculate approximate asymptotic distribution functions for a number of well-known unit root and cointegration test statistics. These allow empirical workers to calculate approximate P values for these tests. The results of the paper are based on a very extensive set of Monte Carlo experiments, which yield finite-sample critical values for a number of sample sizes. Response surface regressions are then used to obtain asymptotic critical values for a large number of different test sizes. Finally, regression methods are used to estimate approximate distribution functions with simple functional forms.
Keywords: 330